Correlation Analysis Between Commodity Market And Stock Market During A Business Cycle (International Journal of Scientific Research and Management (IJSRM), 2015)
The past few years have seen an unprecedented rise in the investments in the new types of financial instruments particularly being the commodity – by directly purchasing commodities, by taking outright positions in commodity futures, or by acquiring stakes in exchange-traded commodity funds (ETFs) and in commodity index funds. This pattern has accelerated in the last few years. In this paper we have compared the returns on the equity and commodity market over the year 2003-2011 for Indian market the data have been taken for nifty and Comdex from year 2003 to 2010. Which is further divide in Business Cycle like the period between 2003-2007 shown a inflationary market, in the same manner the period between 2007-2009 shown a recession and thereafter from 2009-2011was a period of recovery of Indian markets. The correlation is calculated between both the forms of investments over the different periods of investment in Indian history. This paper helps us to understand of trading investments during a business cycle, this also helps us to check the various changes in these markets time to time and understanding us the way of investment during a Business Cycle.